Vocational High School Students’ Challenges in Practicing English Speaking Skills - Talia Milania; Kelik Wachyudi; Mobit Mobit (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
The article overview discussed Indonesian students' challenges in learning English as their second language. Even though English has been added to the school curriculum here in Indonesia from an early age, in reality, there are still many students that have difficulty when learning all the aspects of English skills, especially the speaking aspect. This research aim is to explain students' experiences of their challenges when practicing English speaking skills. By using qualitative methods and a narrative inquiry approach, the data in this study will be collected through short interviews with third-grade students of Vocational high school. The results of the study stated that the challenges faced by students came from various internal and external factors. The conclusion states that even though they have known English since early school, high school students still face difficulties in practicing English speaking skills. This study will explain in detail each influencing factor based on the experiences of these students.